2020
DOI: 10.1002/wer.1423
|View full text |Cite
|
Sign up to set email alerts
|

Coliform bacteria in San Pedro Lake, western Mexico

Abstract: Urbanization, livestock activities, and rainfall are factors that contribute to the contamination of inland water. This study aimed to determine the spatial and temporal variability of total coliforms (TCs) and fecal coliforms (FCs) in the surface water of San Pedro Lake as well as the gills and skin of Nile tilapia (Oreochromis niloticus) cultivated in the lake. The study consisted of seasonal sampling during an annual cycle. Using the multiple‐tube fermentation technique, we quantified the microbial load of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Our results suggest that surface runoff, even after light rainfall (<2.5 mm of rain) is major driver which contributing diffuse pollution both in surface and bottom waters in the pond. This result is consistent with previous studies reported positive correlation between coliform bacteria and rainfall events at lake and pond ecosystems (An et al, 2002; Jeon et al, 2019; Moshi et al, 2022; Ramos‐Ramírez et al, 2020; Staley et al, 2012; Staley et al, 2013; Stocker et al, 2019; Tryland et al, 2011; Xue et al, 2018). On the other hand, few studies reported no significant relationship between fecal indicator bacteria and rainfall (Nguyen et al, 2016; Sampson et al, 2006).…”
Section: Resultssupporting
confidence: 92%
“…Our results suggest that surface runoff, even after light rainfall (<2.5 mm of rain) is major driver which contributing diffuse pollution both in surface and bottom waters in the pond. This result is consistent with previous studies reported positive correlation between coliform bacteria and rainfall events at lake and pond ecosystems (An et al, 2002; Jeon et al, 2019; Moshi et al, 2022; Ramos‐Ramírez et al, 2020; Staley et al, 2012; Staley et al, 2013; Stocker et al, 2019; Tryland et al, 2011; Xue et al, 2018). On the other hand, few studies reported no significant relationship between fecal indicator bacteria and rainfall (Nguyen et al, 2016; Sampson et al, 2006).…”
Section: Resultssupporting
confidence: 92%
“…For this reason, E. coli is an accurate indicator of fecal contamination due to its constant presence in the intestine and feces of warm-blooded animals. The presence of TtC in any body of water has a high predictive value for the potential presence of other pathogenic microorganisms for humans [19][20][21]30 . On the other hand, it has been suggested that the presence of IE might be used as a supplementary test for assessing water quality.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, bacteriological markers have been used to monitor and verify the quality of water intended for human use and consumption, including the presence and count of total coliforms (TC), thermotolerant coliforms (TtC) and intestinal enterococci (IE) [15][16][17][18] . Among the thermotolerant coliforms, Escherichia coli has been considered the most robust fecal indicator 15,16,[19][20][21] . Furthermore, the phylogenetic distribution of E. coli has been suggested as a complementary analysis to help better understand its presence in waters 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used indicators include coliform bacteria, which may have been reduced from total coliform to fecal coliform and faecal Streptococci (Kistemann et al, 2002). Commonly used indicators include coliforms, which may have been reduced from total coliforms to faecal coliforms and faecal Streptococci (Messner et al, 2017;Ramos-Ramírez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%